Modulation of Neuronal Potassium Channels During Auditory Processing - Wu, Jing; Kaczmarek, Leonard K. (Frontiers in Neuroscience, 2021)
The extraction and localization of an auditory stimulus of interest from among multiple other sounds, as in the ‘cocktail-party’ situation, requires neurons in auditory brainstem nuclei to encode the timing, frequency, and intensity of sounds with high fidelity, and to compare inputs coming from the two cochleae. Accurate localization of sounds requires certain neurons to fire at high rates with high temporal accuracy, a process that depends heavily on their intrinsic electrical properties. Studies have shown that the membrane properties of auditory brainstem neurons, particularly their potassium currents, are not fixed but are modulated in response to changes in the auditory environment. Here, we review work focusing on how such modulation of potassium channels is critical to shaping the firing pattern and accuracy of these neurons. We describe how insights into the role of specific channels have come from human gene mutations that impair localization of sounds in space. We also review how short-term and long-term modulation of these channels maximizes the extraction of auditory information, and how errors in the regulation of these channels contribute to deficits in decoding complex auditory information.